Parenting dan Pelibatan Orang Tua pada Lembaga Pendidikan Anak Usia Dini - Ahmad Aly Syukron Aziz Al Mubarok (Universitas Al-Hikmah Indonesia, 2018)
This study aims to find and describe parenting and parent involvement in early childhood education. Parenting is a form of activities undertaken to align parenting activities while Parental involvement is the participation of parents in the education of children both at school and at home. Early childhood education is an effort of coaching to children from birth to age six years through the provision of educational stimulus to help the development and growth so that children have the readiness to enter further education. To balance this, parents are also involved in it by educating children in the home environment. This research is a qualitative research with case study of several RA / Early childhood education schools in Mojokerto, Sidoarjo and Pasuruan.